PDTM-45. POSITIVE MODULATION OF NATIVE GABAA RECEPTORS IN MEDULLOBLASTOMA CANCER CELLS WITH BENZODIAZEPINES INDUCES RAPID MITOCHONDRIAL FRAGMENTATION AND TP53-DEPENDENT, CELL CYCLE-INDEPENDENT APOPTOSIS. (5th November 2018) - Kallay, Laura; Keskin, Havva; Ross, Alexandra; Moody, Olivia; Cottrill, Kirsten; Nuckols, Austin; Li, Guanguan; Ahmed, Taukir; Rashid, Farjana; Stephen, Michael; Xu, Maxwell; Martinson, Deborah; et al.
Abstract: Medulloblastoma is the most common childhood malignant brain tumor. Children with highest morbidity have tumors that are TP53 wild-type and express high levels of MYC and GABRA5, which codes for the α-5 subunit of the ligand (chloride) gated GABAA receptor. Previously, we have established that the α-5 subunit of the GABAA receptor contributes to the assembly of a functional receptor in a subset of medulloblastoma cells and benzodiazepines, synthesized to function as α-5 selective ligands with psychotropic activity, impair viability 1, 2 . Utilizing a TP53 wild-type medulloblastoma cell line with amplified MYC, high GABRA5 expression, and a functional α-5 GABAA receptor, we provide insight into how benzodiazepines impair cell viability by positively modulating the native GABAA receptors. We screened benzodiazepines to assess impact of varying chemical group identity on cell viability. The most potent benzodiazepine binds with specificity to ~1000 native receptors per cell with EC50 and IC50 values of ~0.8 micromolar. This binding evokes a 2 x 10 9 ions.sec-1 chloride flux, which morphologically elicits mitochondrial fragmentation, nuclei distention, and cellular blebbing. The cascade of events culminates in a caspase-mediated activation of apoptosis through the intrinsic pathway and a localization of pro-apoptotic Bcl-2-associated death promoter (BAD) protein. Benzodiazepines may be efficacious as anti-cancer therapeutics for medulloblastoma patients exhibiting a GABAA receptor expression signature by driving a chloride imbalance that leads to cell apoptosis. References: 1 Sengupta, et al. α5-GABAA receptors negatively regulate MYC-amplified medulloblastoma growth. Acta Neuropathol. 2014; 127(4): 593–603. 2 Jonas, et al. First in vivo testing of compounds targeting Group 3 medulloblastomas using an implantable microdevice as a new paradigm for drug development. J. Biomed. Nanotechnol. 2016; 12(6): 1297–1302.